2014
DOI: 10.1159/000356262
|View full text |Cite
|
Sign up to set email alerts
|

Limited Significance of Activated Akt-Mammalian Target of Rapamycin Signaling Pathway in Prostate Cancer Progression

Abstract: Objective: The objective of this study was to investigate the significance of the activated Akt-mammalian target of rapamycin (Akt-mTOR) signaling pathway in the progression of prostate cancer. Materials and Methods: The expression levels of Akt, phosphorylated Akt (p-Akt), mTOR and phosphorylated mTOR (p-mTOR) in 175 prostate specimens, including 61 normal prostate tissues as a control, 24 high-grade prostatic intraepithelial neoplasias (HGPINs) and 90 clinically localized prostate cancers, were evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Recently, the Akt-mammalian target of rapamycin and the Hedgehog signaling pathways have been implicated in the development and progression of PC (Ko, Miyake, Behnsawy, Cheon, & Fujisawa, 2014, Slusarz et al, 2010. In this study, we demonstrate that AMD3100…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Recently, the Akt-mammalian target of rapamycin and the Hedgehog signaling pathways have been implicated in the development and progression of PC (Ko, Miyake, Behnsawy, Cheon, & Fujisawa, 2014, Slusarz et al, 2010. In this study, we demonstrate that AMD3100…”
Section: Discussionsupporting
confidence: 58%
“…PC is one of the most common malignant tumors in men with increasing incidence and mortality rates in China (Ye & Zhu, ). Recently, the Akt‐mammalian target of rapamycin and the Hedgehog signaling pathways have been implicated in the development and progression of PC (Ko, Miyake, Behnsawy, Cheon, & Fujisawa, , Slusarz et al, ). In this study, we demonstrate that AMD3100 inhibits EMT and metastasis of PC cells by blocking the SDF‐1α/CXCR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis, 4 studies [14, 1618] with 736 patients with PCa were identified as eligible for the forest plot after the evaluation of the association between immunostaining and BCR.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because of their very restricted normal tissue expression, immunotherapy targeting CTAs is expected to be more specific and less toxic. Like other members of the CTA family such as MAGE, NY-ESO-1 and SSX2, XAGE-1 has been identified and shown to be expressed in various tumors [15,16,17]. Among the four transcript variants, XAGE-1a, XAGE-1b, XAGE-1c and XAGE-1d, XAGE-1b was identified as a dominant antigen recognized by serum from PCa patients.…”
Section: Discussionmentioning
confidence: 99%